2020
DOI: 10.1016/j.mehy.2020.110114
|View full text |Cite
|
Sign up to set email alerts
|

SIDS, prone sleep position and infection: An overlooked epidemiological link in current SIDS research? Key evidence for the “Infection Hypothesis”

Abstract: Mainstream researchers explain the etiology of SIDS with the cardiorespiratory paradigm. This has been the focus of intense study for many decades without providing consistent supporting data to link CNS findings to epidemiological risk factors or to the usual clinicopathological findings. Despite this, and the apparent oversight of the link between prone sleep position and respiratory infection, papers citing CNS, cardiac and sleep arousal findings continue to be published. Discovery of the prone sleep positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…By contrast, Elhaik [ 18 ] showed that gender bias varies widely between population groups and states and that male neonatal circumcision (MNC) explains 16% of the variability in male SIDS deaths in the US. This finding supported the “wear and tear” hypothesis for SIDS [ 17 ], which explains the main characteristics of SIDS, namely male predominance (60:40) by MNC, the significantly different SIDS rate among USA Hispanics (80% lower) compared to whites by the different circumcision practices of these populations, the 50% of cases occurring between 7.6 and 17.6 weeks after birth, with only 10% after 24.7 weeks by the weaning from the maternally acquired antibodies that protect from infections, and the seasonal variation with most cases occurring during winter by the rise of infections (see the “Infection Hypothesis” [ 90 ]) that increase the allostatic load [ 17 ] (summarized in Table 1 [ 17 ]).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Elhaik [ 18 ] showed that gender bias varies widely between population groups and states and that male neonatal circumcision (MNC) explains 16% of the variability in male SIDS deaths in the US. This finding supported the “wear and tear” hypothesis for SIDS [ 17 ], which explains the main characteristics of SIDS, namely male predominance (60:40) by MNC, the significantly different SIDS rate among USA Hispanics (80% lower) compared to whites by the different circumcision practices of these populations, the 50% of cases occurring between 7.6 and 17.6 weeks after birth, with only 10% after 24.7 weeks by the weaning from the maternally acquired antibodies that protect from infections, and the seasonal variation with most cases occurring during winter by the rise of infections (see the “Infection Hypothesis” [ 90 ]) that increase the allostatic load [ 17 ] (summarized in Table 1 [ 17 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of research, mainstream researchers have not been able to establish a connection between SIDS and reproducible and broad-sweeping neuropathological findings [ 40 , 41 ]. The only remarkably consistent gross pathological findings in SIDS are heavy fluid-laden lungs, intrathoracic petechial hemorrhages, and liquid (unclotted) blood, as described previously.…”
Section: Reviewmentioning
confidence: 99%
“…The important role of infection in SIDS has been described previously [ 40 ] and cannot be overstated [ 41 ]. A plausible mechanism would be an abnormal response to viral respiratory infection when the infant is challenged by a bacterial toxin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…African American infants in the U.S. experience Sudden Unexpected Infant Deaths at twice the rate of white infants (at 186.9 infant deaths per 100,000 live births and 84.9, respectively) [ 1 ]. Risk for Sudden Unexpected Infant Death and SIDS has been suggested using, for example, the infection hypothesis [ 2 ] and the triple risk hypothesis [ 3 , 4 ], which suggest potential underlying vulnerability that may be exacerbated by modifiable behaviors such as maternal smoking, lack of breast feeding, unsafe sleep surfaces, and prone sleeping. Most sleep-related infant deaths occur in environments that have at least one modifiable behavioral risk factor [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%